Partisipasi Publik dalam Proses Menuju Indonesia Baru Evaluasi Terhadap Perkembangan Pemerintahan - Leo Agustino (Unisia, 2005)
When Soeharto's rule begin, in public administration sphere, Indonesia have been emphasizing too much in accommodate the interest of power elite rather than a public interest, it made a public administrator acted like an elite interest want. This image caused a lot of perspectives that public administration in Indonesia do not exist properly. Cause they acted and worked as an "Abdi Negara" rather than "Abdi Masyarakat”. The ongoing of political constelation in1998 was giving a way to introduce a new paradigm of administration-mainstream from the state-oriented-administration to the public-oriented-administration. For that reason, public participation in public administration reform is a realistic idea to be implemented.